Impact Of Corporate Governance On The Quality Of Financial Reports (An Field Study On The Listed Companies In Damascus Securities Exchange) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to determine the degree of impact of the compliment of listed companies in Damascus Securities Exchange to the principles of corporate governance on the quality of the financial reports during the period (2012-2021). To achieve this objective, The researchers used the hypothetical-deductive approach to formulate the hypotheses, and the multi-regression analysis for test these hypotheses. The results of the study came to confirm what was indicated by the administrative literature about the importance of commitment to applying corporate governance in improving the quality of financial reports. The results of the regression analysis showed a relationship between governance mechanisms represented by: managerial ownership, ownership of major shareholders, size of the board of directors, audit committee experience, debt financing, and the ratio of market value to book value of equity (MTB) as a measure of the quality of financial reports. While the variable of board independence had no role in improving the quality of financial reports in the companies under study.